2008
DOI: 10.1007/s11881-008-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Training reading fluency: is it important to practice reading aloud and is generalization possible?

Abstract: Outcomes of three different types of computerized training in sub-lexical items (word-initial consonant clusters) on reading speed for 39 German-speaking poor readers in Grades 2 and 3 were evaluated. A phonological-orthographic association group, a reading aloud group, and a combined group were compared in performance with an untrained control group. During short-term training, the intervention groups showed higher gains than the control group in reading speed of the trained sub-lexical items and of the words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 53 publications
3
49
1
1
Order By: Relevance
“…However, such studies have usually included orthographic neighbor words as control words, and studies investigating generalization from the sublexical level to the word level are lacking. In the previously mentioned study by Hintikka et al (2008), a generalization effect from the sublexical level to word reading was found. Two differences occurred between these studies: In the study by Hintikka et al (2008), the training program was designed to emphasize more clearly fast responding, and the experimental reading task was more congruent with the training program than in the present study.…”
Section: Test Sessionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, such studies have usually included orthographic neighbor words as control words, and studies investigating generalization from the sublexical level to the word level are lacking. In the previously mentioned study by Hintikka et al (2008), a generalization effect from the sublexical level to word reading was found. Two differences occurred between these studies: In the study by Hintikka et al (2008), the training program was designed to emphasize more clearly fast responding, and the experimental reading task was more congruent with the training program than in the present study.…”
Section: Test Sessionmentioning
confidence: 67%
“…On the basis of the accuracy results of the trained items at the sublexical level (the post hoc analysis), this transfer to sounding-out was not a particular problem, as in both tasks (selection and pronunciation), an improvement was found. In addition, in another study, Hintikka, Landerl, Aro, and Lyytinen (2008) decided to contrast practice in reading aloud with the training of the associations between the phonological and orthographic units. It was found that these two training types were equally effective in terms of reading outcomes; thus, association practice can produce positive effects on reading aloud, on production task.…”
Section: Test Sessionmentioning
confidence: 99%
“…In this context, the results of Thaler, Ebner, Wimmer and Landerl (2004) as well as Hinitikaa, Landerl, Aro, and Lyythinen (2008) showed that it is possible to increase the reading speed by a repeated confrontation with frequently occurring sublexical units. Nevertheless, the positive effects are strongly limited to the trained word material and transfer to general reading abilities is conspicuously rare.…”
Section: Intervention Optionsmentioning
confidence: 96%
“…Es werden Aufgaben durchgeführt, in welchen Wortteile (Phoneme, Silben und Morpheme) erkannt, Wörter in kleinere Teile (Laute, Silben, Morpheme) zu untergliedern sind oder Wortteile zu Wörtern zusammengefügt werden müssen (Berninger et al 1999;Magnan et al 2004;Veuillet et al 2007;Ecalle et al 2009). Teilweise werden auch Buchstabengruppen, die eine hohe Vorkommenshäufigkeit in Wörtern aufweisen und dort durch schwierig zu erlesende oder zu verschriftlichende Konsonantencluster gekennzeichnet sind, als Übungsmaterial verwendet (Hintikka et al 2008). Diese…”
Section: Diskussionunclassified